Diseño de una área de recreación turística en la cascada "El Imán", provincia de Los Ríos, año 2019 - Cañar Merelo, Luisana Antonela (2019)
The current research project was conducted in the parish Patricia Pilar in order to raise awareness of the importance of leveraging existing tourism resources within the natural attractions of the place, through the proposal of designing a recreation area tourism in the waterfall "the Magnet", in order to promote tourism and economic development of the inhabitants of the area. In the present investigation it was performed one diagnosis of the current situation of the appeal, where through collecting data and information obtained by the method of field research, it was possible to identify the variety of species in the cascade, in addition to verifying a notable absence of tourist facilities in study area. On the other hand using the technique of survey of the economically active population of the parish, it was determined that implementation of the proposal reached 100% acceptance level. Finally design an area of tourist recreation in the cascade, in which each of the tourist facilities with which to tell the project described also presented an overview table of the budget allocated to the construction of the facility and developed the final design where the location of each of the areas that are part of the recreation area is. KEY WORDS: Recreation, economic development, tourist facilities, proposal, design.